Prevalência das enteroparasitoses em escolares após Programa de Saneamento Ambiental (Bahia Azul) realizado em Salvador, BA - Rodrigues, Letícia Charantola [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Introduction: The intestinal parasites continue to represent a significant public health problem, due to the large number of infected people and the various organic changes that can cause. The intestinal parasites become more prevalent in villages with high population density absence or inadequacy of sanitation and adequate, and personal hygiene practices and inadequate housing. Objective: To determine the prevalence of intestinal parasites Ascaris lumbricoides, Trichuris trichiura and Giardia duodenalis in children of school age (7-14 years) living in the city of Salvador, Bahia, which were part of the Environmental Sanitation Program (Bahia Azul) covering eight different sewage basins in the years 1997/1998 and 2003/2004. Methods: Data were collected pre-coded questionnaire administered to the parents of students, collecting information socioeconomic, environmental and housing conditions. Stool samples were analyzed for each school in the Laboratory of Parasitology of the ISC, UFBA. The database was built and analyzed by Epi Info program (version 3.5.1/2008) were built where overall prevalence rate and Basin depletion of parasites. We compared the overall prevalence rates (at least one parasite) before and after the intervention health, as well as species of parasite. Results: The overall prevalence before the intervention was 56,2% (N = 729) and 42,5% after the intervention (N = 890), down -24,5%. The prevalence observed for each species A. lumbricoides, T. trichiura and G. duodenalis before intervention was respectively 31,4%, 35,8% and 9,9% respectively after the intervention and 24,4%, 28,8% and 6,0%. In relation to variations in prevalence were found to decrease A. lumbricoides, T. Trichiura and G. duodenalis respectively -22,4%, -19,7% and -39,7%. When the results were compared by Basin exhaustion, it was observed that the greatest variation with reduction occurred among students Basin M. Camurujipe to at least one parasite (-51,4%), ...

Introdução: As enteroparasitoses continuam representando um significativo problema de saúde pública, em razão do grande número de pessoas infectadas e das diversas alterações orgânicas que podem ocasionar. Os parasitas intestinais tornam-se mais prevalentes em aglomerados populacionais de alta densidade demográfica com ausência ou insuficiência de condições de saneamento básico adequadas, além de práticas de higiene pessoal e habitações inadequadas. Objetivo: Determinar a prevalência dos enteroparasitas Ascaris lumbricoides, Trichuris trichiura e Giardia duodenalis em crianças de idade escolar (7-14 anos) residentes na cidade de Salvador, BA, que fizeram parte do Programa de Saneamento Ambiental (Bahia Azul), abrangendo oito diferentes Bacias de Esgotamento sanitário nos anos de 1997/1998 e 2003/2004. Métodos: Os dados foram coletados por questionário pré-codificado aplicado aos pais dos escolares, coletando informações socioeconômicas, condições de moradia e ambientais. Amostras de fezes de cada escolar foram analisadas no Laboratório de Parasitologia do ISC, UFBA. O banco de dados foi confeccionado e analisado pelo Programa Epinfo (versão 3.5.1/2008) onde foram construídas taxa de prevalência total e por Bacia de Esgotamento dos parasitas. Foram comparadas as taxas de prevalência total (pelo menos um parasita) antes e após a intervenção sanitária, bem como por espécie de parasita. Resultados: A prevalência total antes da intervenção foi de 56,2% (N=729) e de 42,5% após a intervenção (N=890), com redução de - 24,5%. A prevalência por espécie observada para A. lumbricoides, T. trichiura e G. duodenalis antes da intervenção foi de respectivamente 31,4%, 35,8% e 9,9% e após a intervenção respectivamente 24,4%, 28,8% e 6,0%. Em relação às variações na prevalência, foram encontradas redução para A. lumbricoides, T. Trichiura e G. duodenalis respectivamente de -22,4%, -19,7% e -39,7%. ...
Keywords: Doenças parasitarias; Intestinos - Parasitos; Saúde pública; Higiene escolar; Saneamento; Public health